Parity As A Risk Factor Of Children With Cleft Lip - Widayanti, Nurina; Danila, Amira; Syohanda, Wahyu Indra (Lingkar Studi Bedah Plastik Foundation, 2017)
Background: Cleft lip and palate is one of the most common congenital anomalies with the prevalence of 1 case for every 1000 birth. Nulliparity has been associated with increased of many birth defects. In contrast, multiparity has also been associated with several birth defects. Methods: This case-control study compares data from 74 cleft lip patients who was enrolled in Gentur Cleft Foundation to those of 87 normal children. The dependent variable of this study was the incidence of CL/P (cleft lip with or without cleft palate) and the independent variables were maternal parity. Binary logistic regression was used to analyze crude and adjusted OR. Nulliparous mothers were treated as the reference category. Result: Compared to nulliparous mothers, primiparous mothers has OR 1.57 (95%CI=0.78-3.2). While multiparous mothers has OR 27.54 (95%CI=3.5-216.32). P-value was insignificant for the association of primiparous mothers with CL/P Conclusion: We observe higher incidence of multiparous mothers with the incidence of CL/P compared to nulliparous mothers.